Importance and level of adoption of food safety tools in foodservices. Issue 5 (3rd September 2019) - Araújo, Wilma M. C.; Zandonadi, Renata P.; Tenser, Carla M. R.; Farage, Priscila; Ginani, Verônica C.
ABSTRACT: We evaluated if foodservices (members of the Brazilian Association of Bars and Restaurants) adopt the proposed procedures of the Good Manufacturing Practices (GMP) and the Sanitation Standard Operating Procedures (SSOP) and if they consider these food safety tools important. An instrument evaluated 74 establishments with 43 questions regarding the implementation of food safety tools. Sixty-five percent of the establishments had fully implemented GMP. Ninety-three percent of the establishments considered a very important issue the production of contamination-free products. Seventy-two percent of them considered wastage reduction another important item. Ninety-one percent reported having the GMP's Manual . As to the SSOP, 97% of the establishments referred knowing them; 89% reported adopting them and 63% reported fully adopting them. Only 15% considered the GMP a continuous process, which evinces the lack of awareness of managers and establishment owners in regard to the importance of using these tools in a systematic way.